Buddhist Climate and Buddhist Instruction on Student’s Moral Behavior in Watvachirathammasatit School, Bangkok - Yang, Yan Han (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง; Vol 2 No 1 (2019): ปีที่ 2 ฉบับที่ 1 ประจำเดือนมกราคม - มิถุนายน 2562, 2019)
The purpose of this study is to examine the level of Buddhist Climate, Buddhist Instruction on Student’s moral behavior in Watvacharthammasatit School, Bangkok towards perception in only grade 6 of students based on the independent variables of Buddhist Climate and Buddhist Instruction. Both quantitative and qualitative research methods were applied. The data for this study were collected from  231 students in grade 6 using questionnaires, and 5 five key informants such as, one school principal, and two vice-principals, and two teachers who teach in grade 6 level. Descriptive statistics (frequency, percentage, mean, and standard deviation), and Multiple Regression Analysis were used to analyze the quantitative data, while the content analysis was used to analyze qualitative data. The findings of this research showed that The level of Buddhist Climate and Buddhist Instruction and Student’s moral behavior were overall at the highest level, while Buddhist Instruction was accounted the mean score of 3.48.the following as Buddhist Climate and Student’s moral behavior, with mean scores of 3.41 and 3.28, respectively. to study the effect of Buddhist Climate and Buddhist Instruction on student’s moral behavior.it showed that the overall was at the highest in both components, while the Buddhist instruction was higher than Buddhist Climate with mean scores of 3.48 and 3.4,respectively.and the Regression has showed that :1.34+35(Buddhist climate)+.30(Buddhist instruction) 3.to study the key factor, problem, and obstacles in improving the student’s moral behavior. I showed that it is related to school principals, teachers and parents as good moral model, to practice Buddhist instruction, like five precepts, sitting meditation as well as attending religious activities regularly. It is recommended that concerned authorities, like the Ministry of Education,the Department of Basic Education and  school figures and parents as model and do need to support the strategies for teaching more Buddhist instruction and improve teaching Buddhist climate to students. Key Words : Buddhist Climate, Buddhist Instruction, Moral Behavior.